Supply Chain Integration Capability: An Organizational Routine Perspective - Juan Pablo Escorcia-Caballero; Maria Dolores Moreno-Luzon; Odette Chams-Anturi (International Journal of Supply Chain Management, 2019)
Previous research suggests that the inconsistent results about the relationship between supplier chain integration and performance are due to incomplete and inappropriate conceptualization of supply chain integration dimensions. Therefore, since the resource-based view has been recognized as the most suitable framework to understand these capabilities, we identify and examine routines bundles that make up them. This paper contributes to expand the organizational routines research and provide theoretical guideline for future research in the supply chain management field.